IMPLEMENTASI PENYAJIAN LAPORAN KEUANGAN PADA SEKOLAH SWASTA DI KABUPATEN KEDIRI BERDASARKAN ISAK NO. 35 - Diana, Ike Rika (Universitas Nusantara PGRI Kediri, 2022)
This research is motivated by the number of non-profit organizations that do not understand how to prepare financial reports in accordance with financial standards that apply in Indonesia. The purpose of this study is to analyze whether the financial statements are in accordance with financial accounting standards and implement financial statements based on ISAK No 35. This study uses a qualitative approach with a descriptive method. The result of this research at SMK Pemuda has made a daily cash income and expenditure journal. However, SMK Pemuda still has not recorded financial statements in accordance with ISAK No. 35 due to lack of socialization about ISAK No 35. SMK Pemuda only presents general journals, activity reports and balance reports. While in ISAK No. 35 financial statements consist of statements of financial position, statements of comprehensive income, statements of changes in net assets, statements of cash flows and notes to financial statements.